Konseling Laktasi Intensif dan Pemberian Air Susu Ibu (ASI) Eksklusif Sampai 3 Bulan - Ria Ambarwati; Siti Fatimah Muis; Purwanti Susantini (MEDIA MEDIKA INDONESIANA, 2012)
Intensive lactation counseling and exclusive breastfeeding up to 3 monthsBackground: In 2010 within the area of Semarang Municipality, exclusive breastfeeding by mothers to their babies reaches up to only 20,06%. One of the problems is the lack of lactation counseling especially by the health service institutions.Objectives: To reveal the effect of intensive lactation counseling on exclusive breastfeeding up to 3 months.Method: This research study is designed as a quasi-experiment of non-equivalent control group. The population of this study is a group of mothers who were in the 7th to 8th months of pregnancy bearing the second child or more. The number of the subjects is 25 mothers who were grouped into 2, that is the experimental groups of 12(n=12) and control group of 13 (n=13). The group underwent a treatment of intensive lactation counseling of 9 times on 2 stages, the first was four-time treatments during the medical examination on their pregnancy of 7th-8th months. The second stage of treatments was done by home visit for 5 times during week 1, 2, 4, 8, and 12 after giving birth by sertified lactation counselors for 40 workhours. These counselors had the experience of at least 5 clients counseling. The control group got the usual counseling that they normally received from the midwives at the Health Primary Center and private midwives nearby.Results: The group without intensive lactation counseling shows no gain of knowledge, attitude towards early initiation of breastfeeding, exclusive breastfeeding, breastmilk and no increase of the number of exclusive breastfeeding on their babies prior to and during the study. The group with intensive lactation breastfeeding shows a significant gain in every aspects being studied and significant increase (five fold) of the number of exclusive breastfeeding on their babies that born prior to and during the study from2(16.7%) to 10(83.3%).Conclusion: Intensive lactation counseling increases the practice of exclusive breastfeeding up to 3 months and should be performed by health care delivery system.Keywords: Intensive lactation counseling, exclusive breastfeeding, 3 months ABSTRAKLatar belakang: Ibu yang memberikan ASI eksklusif di Kota Semarang Tahun 2010 hanya mencapai 20,06%. Salah satu penyebabnya adalah kurangnya konseling laktasi di sarana pelayanan kesehatan.Tujuan: Mengetahui pengaruh konseling laktasi intensif terhadap pemberian ASI eksklusif sampai 3 bulan.Metode: Penelitian dengan rancangan quasi experiment non equivalent control group. Populasi adalah ibu hamil trimester 3 dengan usia kehamilan 7-8 bulan pada anak kedua atau lebih. Jumlah sampel 25 ibu hamil yang dikelompokkan menjadi 2 yaitu kelompok perlakuan (n=12) dan kelompok kontrol (n=13). Kelompok perlakuan mendapat konseling laktasi intensif sebanyak 9 kali yaitu 4 kali pada saat pemeriksaan kehamilan umur 7-8 bulan dan kunjungan rumah sebanyak 5 kali pada minggu ke-1, 2, 4, 8, 12 setelah kelahiran oleh konselor laktasi yang memiliki sertifikat pelatihan konselor laktasi. Kelompok kontrol mendapat konseling pada pemeriksaan kehamilan yang selama ini dilakukan oleh bidan di Puskesmas dan Bidan Praktik Swasta.Hasil: Pada kelompok yang tidak mendapat konseling laktasi intensif tidak ada perubahan skor pengetahuan, sikap terhadap inisiasi menyusu dini, ASI eksklusif, ASI, menyusui dan tidak ada peningkatan jumlah ibu yang memberikan ASI eksklusif sampai 3 bulan pada anak yang dilahirkan sebelum dan selama penelitian. Kelompok yang mendapat konseling laktasi yang intensif menunjukkan ada perubahan skor pada semua anak dan peningkatan jumlah ibu yang memberikan ASI eksklusif sampai 3 bulan pada anak yang dilahirkan selama penelitian menjadi 5 kali lipat.Simpulan: Konseling laktasi intensif dapat meningkatkan jumlah ibu yang melaksanakan ASI eksklusif sampai 3 bulan dan perlu dilaksanakan oleh semua sarana pelayanan persalinan.